Feeling the heat: responses to geothermal development in Kenya's Rift Valley. Issue 2 (2nd April 2020) - Hughes, Lotte; Rogei, Daniel
ABSTRACT: Geothermal development in Kenya's Rift Valley will reap enormous energy benefits for the nation as a whole. But its impacts upon local communities, in this case in the Ol Karia area of Nakuru County, are often negative, and geothermal expansion has led to many divisions and conflicts over equitable resource use, environmental degradation, health impacts on humans and animals, forced resettlement, access to benefits including jobs, houses and profit sharing, human and land rights, and community representation vis-á-vis the geothermal companies. Many questions have been raised about the role of the state and international financial institutions (IFIs). Accusations abound at grassroots level of nepotism, corruption and discrimination, and some indigenous residents accuse the majority Maasai of doubly marginalising them in the scramble for rights and benefits. Against a background of historical continuities, land injustices, and global struggles for indigenous and marginalised peoples' rights, this article examines the conflicts and complexities surrounding geothermal development at Ol Karia and its environs, and describes how people on the ground see the prospects for future peaceful co-existence with extractive industry on their lands.